Pengaruh Pelatihan Komunikasi Efektif terhadap Peningkatan Pengetahuan Karyawan RSUD Kota Malang - Emilia Gondowahjudi, Lana; Ratri, Devita Rahmani; Hakim, Lukman (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2018)
The purpose of this study is to determine the effect of effective communication training on knowledge of employees of Malang City Hospital. This research type is quantitative with experiment method. The experimental model used is one group pre-test post-test, where the employees of RSUD Malang will be given two tests, namely the pre-test and the post-test to know the effect of the training given to the improvement of employee knowledge. The results showed that effective communication training provided could encourage the improvement of employees knowledge of RSUD Malang, which was seen in the increase of the average of test result, that is from 49,37 in pre-test to 59,64 in post-test.